Produktivitas Sapi Bali Betina dan Hasil Persilangannya dengan Limousin dan Simmental yang di Pelihara Berbasis Pakan Hijauan di Kabupaten Keerom Papua (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Development of cattle in the Papua region still faces many obstacles, particularly the limited number of cattle population and the quality of the animal dominated by bali cattle. This study aimed to evaluate the productivity of bali cattle and their crosses with limousin and simental through artificial insemination. This study was carried out on December 2016 to February 2017  in the Arso and Skanto Districts, Keerom Regency, Papua. Ninty four heads of used in this study, comprising 57 bali catsle, 18 bali x limousin and 19  bali x simmental crosses through artificial insemination programe. Parameters vanahle included reproduction characteristics, body weight and linear body measurement.  The observation were conducted of calf (25 month).  The results indicated that the female bali cattle and their crosses with limousin and simmental raised on forage based feed showed different reproduction and production perfomances.  The cross bred cow (bali x limousin and bali x simmental) tended to have longer age at first mating, higher service per conception and lower calving rate.  Based on forage feed, the cross bred cow had significantly (P